Development and survivability of ovarian follicles of goat in different feeding systems - Alam, MH; Kabir, ME; Sarker, MB; Saha, BK; Khan, RI; Moniruzzaman, M (Bangladesh Journal of Animal Science, 2014)
The present study was aimed to know the effects of feeding systems on follicular development in Black Bengal goats. Nine female post-weaned Black Bengal goats were randomly assigned to 3 feeding systems namely stall feeding, tethering and grazing. After 240 days of rearing, goats were slaughtered and ovaries were collected for morphometric analysis. Histological examination revealed that the percentages of secondary (p<0.01) and antral follicles (p<0.05) were higher in stall-fed than tethering and grazing goats. Percentage of primordial follicles (61±2%) was lower in stall-fed goats and higher in tethering (71±3%) goats. Number of degenerated follicles was higher in tethering goats and lower in stall-fed groups. These results reveal that development and degeneration of ovarian follicles are influenced by feeding systems of goats. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21644 Bang. J. Anim. Sci. 2014. 43 (3): 175-179